Penambahan Kulit Kacang Tanah pada Medium Jamur Menambah Berat Kering Jamur Tiram Putih - Sedijani, Prapti; Rahmi, Maskatur; Japa , Lalu; Eniarti, Miko (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Medium composition affects the productivity of oyster mushroom. Nutritious ingredient may increase the mushroom productivity. Peanut shell as a leguminous plant is rich in protein content than zea mays bran a common supplement for the medium. This research ach aims to see the influence of peanut shell supplementation at different concentration on productivity of oyster mushroom in comparison to zea mays bran. The concentration used were 0; 3 and 6% of peanut shell or zea mays bran. The parameter observed were the time of primordial pin head appearance; the pin head number, fresh weigh and dry weight of oyster mushroom. The data obtained were analyzed using ONE WAY ANOVA followed by Least Significant Different Test for the significance. The result showed that medium with Zea mays did not show a significant different from control in all parameters used. The peanut shell increased the dray weight of oyster mushroom, the dray weight increase was higher at supplementation of 3% peanut shell than that of 6%. The fresh weight and number fruiting body were not significantly different among all the treatments, however, the average of the fresh weigh and the number of pin-head, were higher found on medium supplemented with peanut shell that others. Three percentage of peanut shell was better than that of 6%.